KEKERASAN VERBAL DALAM UNGKAPAN MAKIAN OLEH MASYARAKAT DI DESA KOTO LAWEH KECAMATAN TANJUANG BARU KABUPATEN TANAH DATAR - Kurniawan, Rio; Agustina, Agustina; Ngusman, Ngusman (Jurnal Bahasa dan Sastra, 2018)
This research was conducted to describe (1) forms of expression of insult, (2) the function of expression, (3) the context of the use of expression of verbal abuse in the village of Koto Laweh Subdistrict Tanjuang Baru Tanah Datar District. This type of research is qualitative research using descriptive method. The subject of this study is a sentence or speech that contains the expression of insults used by the community in the Village Koto Laweh Tanjuang Baru District Tanah Datar. The data taken are analyzed by the following steps: (1) transcribing existing data from various sources into written language, ie from recorded data, interviews, and observations, (2) classifying forms of insults by function and context, (3) ) analyzing the data according to the research objectives, (4) formulating the research findings. There are three findings in this study. First, based on the form, the expression of insults in the verbal violence used by the community in Koto Laweh Village Tanjuang Baru Sub District can be classified into two types (a) expressions of word-shaped, (b) phrase-shaped expressions. Secondly, based on the phrase function of acquired speech in the village of Koto Laweh, there are 7 functions of expression, (1) as a means of expressing resentment, (2) expressing strong and extreme emotions, (3) as joke, means of expressing social intimacy, (5) insulting, (6) expressing frustration and irritation, (7) means of expression of amazement. Third, on the basis of forms of expression it is used in all contexts with reference to four speech situations, ie (a) higher speakers of the position and the relationship is familiar, (b) the speaker is higher in rank and the relationship is not familiar, (c) the speaker is more low his position and the relationship is familiar, (d) the speaker is inferior to his position and the relationship is not familiar.Keywords: form, function, context, invective